Pemanfaatan Lahan Pekarangan untuk Budi Daya Sayuran Secara Hidroponik di Kecamatan Sungailiat, Kabupaten Bangka, Provinsi Kepulauan Bangka Belitung - Rati Purwasih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The aim of community service is to transfer and apply the science and technology of vegetable cultivation with a hydroponic system to a housewive community in Sungailiat District. Community service is carried out to housewive communities in Sungailiat and Sri Menanti Village, Sungailiat District, Bangka Regency, Bangka Belitung Islands Province in September 2018. The counseling methods used are face-to-face communication, lectures, discussions and direct demonstrations to the participants. The results showed that the group of housewives in the two villages had understood the cultivation technique of vegetables with a hydroponic system starting from the preparation of seedling media, seedbed nursery, mixing AB nutrient mix, planting, maintaining, harvesting, as well as maintaining to increase vegetable production as a source of food and family income.